Changes in the bulk soil after fresh corn grown with organic and inorganic fertilizer application. - Riri Dayang Sari Risman; Kiriya Sungthongwises; Supanath Kanjanawattanawong (PLoS ONE)
The effects of different fertilizer applications on crop growth, soil health, and microbial communities are critical for sustainable agriculture. Positive interactions between crop roots and their associated microbiomes are essential to improve nutrient availability and promote plant growth. Therefore, this study aimed to investigate the changes in bulk soil chemical properties and diversity of phosphate-solubilizing microorganisms after growing three fresh corn plants under the application of vermicompost, black soldier flies, and inorganic fertilizers. Fresh corn yield and soil samples were collected from purple waxy, pink waxy, and sweet corn grown under field conditions. The capacity to solubilize mineral phosphate and indole acetic acid was also determined using a spectrophotometer. The results showed that organic and inorganic fertilizers can maintain the ear-fresh weight of the three fresh corn varieties and tend to increase some soil chemicals after growth. Application of inorganic fertilizer and black soldier flies mixed with inorganic fertilizer resulted in the highest ear fresh weight, with 6,291.30 and 5,887.40 kg ha-1, respectively. Moreover, the soil pH, available phosphorus, and copper tended to increase, whereas zinc and chromium decreased. However, fertilizer management did not affect the diversity of the phosphate-solubilizing microorganisms. In addition, the three phosphate-solubilizing fungal isolates were similar to the type strain of Candida tropicalis. The phosphate-solubilizing fungi isolate potentials were not significantly different in AlPO4, and FePO4 solubilizing. Only two PSF isolates from purple waxy produced IAA hormone between 462.81-562.81 mg l-1.